Efektivitas Penerapan Pembelajaran Model Flipped Classroom pada Materi Statistika Kelas VIII - Rusli, Rusli; Nasrullah, Nasrullah; Sannang, Hafsah Halim (Issues in Mathematics Education (IMED), 2024)
This research determine to effectiveness of implementing flipped classroom model on statistics material in grade VIII at SMP Negeri 18 Makassar. The type of this study research is a pre-experimental with One-Group Pretest Posttest Design. The population in the research were all students of grade VIII and VIII.3 as the experimental group, which consisted of 21 students. The instruments used are learning achievement tests, student activity observation sheets, and student response questionnaires. The data analysis technique that used was the technique of descriptive and inferential statistical analysis. The result show that: (1) When viewed from the learning outcomes of students, the average learning outcomes after implementing flipped classroom is 81,14, the average increase in learning outcomes (gain value) is 0,74 in the high category, and the classical completeness of 85%, (2) The average percentage of student activity at each meeting in the implementing flipped classroom is 83,33% in the very active category, and (3) The average percentage of responses each students to the implementation of flipped classroom is 72% in the good category. Based on the effectiveness criteria, which concludes that flipped classroom learning is effectively applied on statistics material in grade VIII at SMP Negeri 18 Makassar